AN ANALYSIS OF TRANSITIVITY IN THE RECOUNT TEXT WRITTEN BY THE TENTH GRADERS OF SMA MUHAMMADIYAH 1 KOTA MAGELANG IN THE SCHOOL YEAR OF 2018/2019 - Yasman Yasman (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
In writing, the students need to understand the role of grammar  include the ideational meaning. However, the tenth graders of SMA Muhammadiyah 1 Kota Magelang in the school year 2018/2019 still got difficulties in writing recount text. Besides, the students should acquire the part of ideational meaning in writing their recount text especially transitivity.The objectives of this research are to describe the types of process, participant, circumstance that are used by the tenth graders of SMA Muhammadiyah 1 Kota Magelang in the school year of 2018/2019 in writing recount texts.The writer conducted discourse analysis. The subject of this research is X IPA 1 involving 10 males and 14 females. The unit of analysis of this study was clauses of the students’ writing recount text. The writer selected the students’ texts which were appropriate with the component of recount text, identified the types of component of transitivity, and calculated the percentage. The results of this research show that there are 328 clauses with 6 types of process, 15 types of participant, and 6 types of circumstance. The writer infers the most dominant aspects of transitivity components are material process, participant of actor, and circumstance of place.